A study on assessment of sleep quality amongst patients attending a rural hospital in Kancheepuram, Tamilnadu, India - Ganesan, Vijayakrishnan; Ganesan, Dinesh Kumar; Fulse, Gayatri; Shah, Jhara (International Journal Of Community Medicine And Public Health, 2019)
Background: Sleep is the state, in which the organism temporarily, partially and periodically loses its interaction with surroundings at different intensities and which can be reversed with stimuli. Sleep deficiency in sleep is linked with many physical ailments. The present study was aimed at assessing the sleep quality of patients attending the outpatient department of a rural health centre in Kacheepuram, Tamilnadu. Methods: A cross sectional study was conducted amongst patients attending the OPD of rural health center of a Medical College Hospital at Kancheepuram. A pretested semi structured questionnaire based on Pittsburgh sleep quality index (PSQI) was used to collect data. Data were entered on and analyzed using Microsoft excel spread sheet. Results: Of the 150 participants who participated in the study 87 (58%) were males and 63 (42%) were females. In the present study there were 80 participants (53.3%) under the age of 40 years and 70 participants (46.7%) over the age of 40 years. Of the 150 participants 85.3% of them had a sleeping time <8 hrs a day and a minority of them 14.7% had a sleeping time of >8 hrs a day. The sleep quality of females was slightly better (54%) when compared to males. It was also observed that only 10 (9.7%) of the skilled workers had good quality of sleep when compared to unskilled workers. Conclusions: Our present study shows, the prevalence of poor-quality sleep was 31.3%. Various factors like gender, occupation and education were found to positively associated with poor quality sleep.